A person-centred approach to L2 learners' informal mobile language learning. Issue 9 (8th December 2022) - Peng, Hongying; Jager, Sake; Lowie, Wander
Abstract: Mobile technologies provide opportunities for L2 learners to engage in complex interactions involving a multitude of cognitive, meta-cognitive, and affective factors. Understanding the process of learners' mobile language learning thus needs holistic approaches that integratively consider learner attributes and their interaction with mobile technologies. In this study, we applied a holistic person-centred approach to examining L2 learners' self-initiated engagement with mobile learning activities. Data were collected with a questionnaire and follow-up interviews. A cluster analysis performed on the questionnaire data yielded six types of learners with distinctly different learning experiences. We further found that each learner type brought along a distinct package of motivational, emotional, and linguistic interaction, and that the distinct learning experiences of each learner type bore different relationship to learners' perceived L2 improvement. This study offers theoretical and methodological insights into the complexity and variety inherent in informal mobile language learning. Findings also inform teachers about the design of adaptive and tailored instruction and scaffolding.